2020
DOI: 10.3390/antibiotics9010036
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Colloidal Silver against Gram-Negative and Gram-Positive Bacteria

Abstract: Due to the emergence of antimicrobial resistance, new alternative therapies are needed. Silver was used to treat bacterial infections since antiquity due to its known antimicrobial properties. Here, we aimed to evaluate the in vitro activity of colloidal silver (CS) against multidrug-resistant (MDR) Gram-negative and Gram-positive bacteria. A total of 270 strains (Acinetobacter baumannii (n = 45), Pseudomonas aeruginosa (n = 25), Escherichia coli (n = 79), Klebsiella pneumoniae (n = 58)], Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 32 publications
3
52
1
Order By: Relevance
“…The intensity of the fluorescence signal is proportional to the amount of ROS [ 28 ]. The research data obtained from previous reports suggest that: treatment with AgNPs alone did not induce significant ROS formation [ 29 ]; a significant increase in the DCF fluorescence intensity was observed for AgNP-treated bacterial cells [ 30 ]; colloidal silver significantly increased the production of ROS when compared with untreated cells [ 31 ]; ROS played a very important role in the antibacterial mechanism of AgNPs [ 32 ]. Interestingly, ROS detection data in AgNP-treated E. coli [ 33 ] showed that the fluorescence signal of AgNP-treated cells is lower than for the non-treated cells, for most treatment concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the fluorescence signal is proportional to the amount of ROS [ 28 ]. The research data obtained from previous reports suggest that: treatment with AgNPs alone did not induce significant ROS formation [ 29 ]; a significant increase in the DCF fluorescence intensity was observed for AgNP-treated bacterial cells [ 30 ]; colloidal silver significantly increased the production of ROS when compared with untreated cells [ 31 ]; ROS played a very important role in the antibacterial mechanism of AgNPs [ 32 ]. Interestingly, ROS detection data in AgNP-treated E. coli [ 33 ] showed that the fluorescence signal of AgNP-treated cells is lower than for the non-treated cells, for most treatment concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…More accessible alternatives are therefore beginning to be developed as photosensitisers. [24][25][26][27][28][29][30] Metal ions such as Ag + , 31,32 metal oxides such as ZnO, 33 and complexes based on various metal ions including Cu(I), 34 have shown to be toxic to bacteria without light; 31,32,34 whilst inherently phototoxic metal nanoparticles have been used together with photosensitisers to promote the photoactivated production of ROS to initiate bacterial killing. 33,35 Other well-known photosensitisers include porphyrins, 36,37 such as derivatives of Zn(II) porphyrazine, or 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin tetra-iodide (tetra-Py + -Me), which have also been used for water treatment with good results: for example, tetra-Py + -Me at 10 mM achieved a reduction of 99.999% of E. coli after 120 min of irradiation with artificial white light (380-700 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the emergence of antibiotic resistance, new alternative therapies are needed. Colloidal silver (CS) shows anti-biofilm properties in multidrug-resistant bacteria [ 61 ]. The suspension of submicroscopic silver particles does not directly attack bacteria but leads to the inactivation of enzymes responsible for bacterial respiration, reproduction, and metabolism by forming homo-base pairs with guanine, targeting sulfhydryl group to form S-silver bonds, and mediating membrane alteration [ 62 ].…”
Section: Compoundsmentioning
confidence: 99%